Evaluation of point-of-care PRO assessment in clinic settings: integration, parallel-forms reliability, and patient acceptability of electronic QOL measures during clinic visits. - Sharma, Pranav; Dunn, Rodney; Wei, John; Montie, James; Gilbert, Scott; Dunn, Rodney L; Wei, John T; Montie, James E; Gilbert, Scott M (Quality of Life Research, 2016)
Purpose: Assessment of patient-reported outcomes (PROs), such as health-related quality of life, has become an important component of healthcare that measures the impact of disease and medical treatment on patient health. Collecting PROs during point-of-care assessments and integrating them into the clinical setting, however, remains challenging. The objective of this pilot study was to evaluate the reliability, usability, and acceptability of point-of-care electronic PRO assessments implemented in a prostate cancer clinic.Methods: Fifty subjects completed paper-pencil and computerized formats of the Expanded Prostate Cancer Index Composite (EPIC), a validated, condition-specific QOL instrument, at separate times before treatment. Parallel-forms reliability was evaluated by comparing mean scores, variations in response distribution, and correlations between administration formats. Correlation coefficients of at least 0.70 were used for reliability testing. Differences between administration forms, indicating potential bias, were compared using the signed-rank test. A 6-item acceptability scale was also used to evaluate patient acceptability and satisfaction with the electronic format.Results: Mean scores and standard deviations were similar between the paper-pencil and electronic forms across all EPIC instrument domains, and no assessment bias was found. Each EPIC domain demonstrated a high reliability between administration formats (correlation coefficients: 0.70-0.98). The majority (>90 %) of respondents found that the computerized QOL format was user friendly and simple to use.Conclusions: Point-of-care computerized QOL assessments were reliable and acceptable to patients in this study, supporting the feasibility of PRO integration at the point-of-care in clinical settings.